Daftar jenis gastropoda dari Pulau Lombok dan pulau-pulau satelitnya - Mujiono, Nova (Jurnal Biologi Udayana; Vol 24 No 2 (2020): JURNAL BIOLOGI UDAYANA, 2020)
Lombok, an island that lies in the Lesser Sunda Islands, is popular for the tourist destination. One attempt to promote tourism is through the biodiversity of its fauna. This study aims are to summarized the diversity of gastropoda and made a checklist to make it easier studied. Museum collections and fifteen works of literature were used as the data source. A total of 74 families and 292 species of gastropoda were documented from 29 locations. Twenty-one species are new records for Lombok Island. About 29% of them have their representation in the museum collections. The list dominated by marine (65%), following by terrestrial (15%), mangrove (6%), and freshwater species (5%). The most diverse family, Neritidae, which occupies wider habitat is represented by nine percent. Littoraria scabra is the most widely distributed species which occurs in 12 locations. The five most diverse locations were marine habitats which popular for tourism destinations. This study contributes to the development of marine ecotourism.